La privacy della mente: alcune riflessioni sul rapporto tra protezione dei dati personali e libertà di pensiero (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Introduzione - 2. Riservatezza psichica, profilazione e neurotecnologie - 3. Il valore della riservatezza psichica - 4. Privacy e libertà di pensiero.Psychoprivacy: Some Remarks on the Relation between Protection of Personal Data and Freedom of ThoughtABSTRACT: This essay maintains that the same normative reasons that lead to ascribe to individuals a fundamental right to privacy imply a fortiori a certain degree of legal protection against the unwanted detection and disclosure of their ideas, beliefs, opinions, preferences, tastes, feelings, moods, dispositions, memories, aspirations, action plans and other conscious or unconscious products of their mind. This aspect of the right to privacy referred to the mental (cognitive, doxastic, intentional, mnemonic and emotional) dimension of individuals will be called psychoprivacy and examined in its relationship with freedom of thought. It will be concluded that the psychoprivacy of individuals conflicts with freedom of thought only if the latter is considered from the perspective of the speaking subject, that is, the one who claims the freedom to express their thoughts without any legal restrictions whatsoever. If, on the other hand, freedom of thought is centered on the thinking subject, and understood as the right to cultivate one's thoughts and purposes regardless of any expression or translation in practice, then there is no conflict with psychoprivacy, but rather harmony.